Analisis Cost Volume Profit (CVP) Sebagai Alat Perencanaan Laba: Studi pada UMKM Keripik Q-Jho, Poncokusumo Malang - Sultoni, Dimas; Yona Octiani Lestari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
MSMEs are in a positive trend with their numbers continuing to increase every year. In determining the selling price of MSME products, they must manage and plan their finances efficiently. Q-Jho Chips MSMEs have never used cost volume profit analysis in planning their profits. CVP analysis will help Q-Jho Chips MSMEs to understand the relationship between production costs, production volume, selling price and profits generated. By understanding this relationship, Q-Jho Chips MSMEs can make smarter decisions regarding setting selling prices, optimal production volumes and cost control strategies. The research method used is a descriptive qualitative research method. The location of this research was carried out at the , Q-Jho Chips MSMEs . The data analysis method used in this research is descriptive with a case study approach. Furthermore, in 2024 Q-Jho Chips wants to increase profits by 5%, so a cost volume profit analysis is carried out. According to the calculations that have been made, it can be seen that the sales that must be made in 2024 are IDR 227,608,575 and generate a profit of IDR 96,442,521.